2021
DOI: 10.2217/epi-2021-0080
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Methylation and Protein Markers is Capable of Detecting Gastric Cancer Detection by Combined Markers

Abstract: Aim: This study aimed to validate a combination of mSEPT9, mRNF180 and CA724 for gastric cancer (GC) detection. Patients & methods: The performance of mSEPT9, mRNF180 and CA724 was examined in a prospective cohort study with 518 participants (151 with GC, 56 with atrophic gastritis, 87 with other gastrointestinal diseases and 224 with no evidence of disease). Results: mSEPT9, mRNF180 or CA724 alone detected 48.3, 37.1 and 43.1% of GC, respectively. The combination of mSEPT9 and mRNF180 detected 60.3% of GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…For the initial review, 95 relevant pieces of literature were obtained. Following the layer-by-layer screening, 9 studies on diagnostic accuracy with 1531 subjects were finally included (2,11,22,(24)(25)(26)(27)(28)(29). Figure 1 depicts the screening process and results of the literature.…”
Section: Search Resultsmentioning
confidence: 99%
“…For the initial review, 95 relevant pieces of literature were obtained. Following the layer-by-layer screening, 9 studies on diagnostic accuracy with 1531 subjects were finally included (2,11,22,(24)(25)(26)(27)(28)(29). Figure 1 depicts the screening process and results of the literature.…”
Section: Search Resultsmentioning
confidence: 99%
“…Moreover, the panel developed in our study also displayed a comparable sensitivity for each UGC type. For example, Xu et al reported a combined methylation assay for GC detection with a sensitivity of 60.3% and a specificity less than 88% [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yongzhan Nie 1,# Xianchun Gao 1,# Xiqiang Cai 2,# Zhen Wu 3,# Qiaoyi Liang 4 Guobing Xu 5 Na Liu 6 Peng Gao 7 Jingyu Deng 8 Hongzhi Xu 9 Zhanlong Shen 10 Changqi Cao 5 Fenrong Chen 6 Nannan Zhang 1 Yongxi Song 7 Mingjun Sun 11 Chengyin Liu 3 Guangpeng Zhou 3 Weili Han 1 Jianhua Dou 1 Huahong Xie 1 Liping Yao 1 Zhiguo Liu 1 Gang Ji 1 Xin Wang 2 Qingchuan Zhao 1 Lei Shang 12 Daiming Fan 1 Xiaoliang Han 3 Jianlin Ren 9 Han Liang 8 Zhenning Wang 7 Jinhai Wang…”
Section: E T H I C S a P P R O Va L A N D C O N S E N T T O Pa R T I ...mentioning
confidence: 99%